A Gaussian Approach for Continuous Time Models of Short Term Interest Rates - YU, Jun (Institutional Knowledge at Singapore Management University, 2002)
This paper proposes a Gaussian estimator for nonlinear continuous time models of the short-term interest rate. The approach is based on a stopping time argument that produces a normalizing transformation facilitating the use of a Gaussian likelihood. A Monte Carlo study shows that the finite-sample performance of the proposed procedure offers an improvement over the discrete approximation method proposed by Nowman (1997). An empirical application to US and British interest rates is given.